EROS AND DESCRIPTIONS OF SPACE IN THE NOVELS OF BORISAV STANKOVIĆ (Philological Studies, 2025)
This paper explores the connection between Eros and space in the novels Gazda Mladen, Nečista krv, and the unfinished work Pevci by Borisav Stanković. Special attention will be paid to the analysis of spatial eroticization, when the Eros felt by the characters spreads through the spaces in which they live, and work, or when the erotic energy is transmitted through the objects they touch, lean on, etc. Using selected examples from the novels, the paper interprets the descriptions of both intimate (family homes, rooms) and public places (shops, bazaars, hammams), in which the Eros of Stanković’s literary characters manifests itself (as repressed, restrained or liberated).
Keywords: Borisav Stanković, eros, poetics of space, novel, erotology